Smooth transition adaptive hybrid impedance control for connector assembly. Issue 2 (12th February 2018) - Wu, Jun; Ni, Fenglei; Zhang, Yuanfei; Fan, Shaowei; Zhang, Qi; Lu, Jiayuan; Liu, Hong
Abstract : Purpose: This paper aims to present a smooth transition adaptive hybrid impedance control for compliant connector assembly. Design/methodology/approach: The dynamics of the manipulator is firstly presented with linear property. The controller used in connector assembly is inspired by human operation habits in similar tasks. The hybrid impedance control is adopted to apply force in the assembly direction and provide compliance in rest directions. The reference trajectory is implemented with an adaptive controller. Event-based switching strategy is conducted for a smooth transition from unconstrained to constrained space. Findings: The method can ensure both ideal compliance behaviour with dynamic uncertainty and a smooth transition from unconstrained to constrained space. Also, the method can ensure compliant connector assembly with a good tolerance to the target estimation error. Practical implications: The method can be applied in the connector assembly by "pushing" operation. The controller devotes efforts on force tracking and smooth transition, having potential applications in contact tasks in delicate environment. Originality/value: As far as the authors know, the paper is original in providing a uniform controller for improving force and position control performance in both unconstrained and constrained space with dynamic uncertainty. The proposed controller can ensure a smooth transition by only adjusting parameters.